Determination of glutamate in food samples by heterogeneous membrane with chitosan as ionophore - Md Isa Illyas, Ab Ghani Sulaiman, (N/A, 2009)
Determination of glutamate in food samples by heterogeneous membrane with chitosan as ionophore by Md Isa Illyas, Ab Ghani Sulaiman,